(untitled) - Joseph S Levine (Lexington, Massachusetts, 1994)
The book consists of seven parts. Part 1 adresses a fundamental aspect of biology: the nature of scientific inquiry and the interaction between science, scientists, and society at large. Part 2 introduces the key themes of evolution and genetics by looking chronologically at the work of Darwin and Mendel. Part 3 presents Darwin and Mendel in their historical context. Part 4 presents basic chemistry, biochemistry, and molecular biology, as well as the experimental foundations for future molecular understanding of genetics, evolution, and artificial evolution (genetic engineeering). Part 5 starts with biological classification and geologic history, biodiversity through a discussion of the probable origins of life on Earth, evolutionary changes over time, and an examinationof current spacies. Part 6 and 7 uses both the macroscopic (ecological and evolutionary) and microscopic (cellular and molecular) perspective to study the functioning of plants and animals
Keywords: biology